A Synthesis Evaluation of Four IFC-Supported Small and Medium Enterprise Facilities - Operations Evaluation Group (International Finance Corporation, Washington, D.C., 2017)
This report summarizes the findings of evaluations of four small- and medium-scale enterprise (SME) facilities sponsored and managed by International Finance Corporation (IFC) to support the development of small businesses. It examines five broad issues. First, it considers relevance, i.e., whether the facilities’ efforts are justified by their likely impact on development. Second, it considers efficacy and impact, i.e., the extent to which the facilities are contributing to the development of sustainable SMEs and business service providers and to improvements in the business climate. Third, it considers efficiency, i.e., the facilities’ own efficiency in providing services and the extent to which the benefits generated justify the overall costs and the subsidies provided. Fourth, it considers the sustainability of the services provided by the facilities and by the business service providers the facilities support. Fifth, it considers some structural and administrative issues, including collaboration among the facilities and with other parts of the World Bank Group; management information systems and reporting; and learning from experience. The study is based primarily on Operations Evaluation Group (OEG)-directed evaluations of four facilities still supported by IFC that are sufficiently mature for evaluation. The individual evaluation reports, which outline the methodologies used, are available on OEG’s website (www.ifc.org/oeg).